Impact of pre-transplant dialysis modality on the outcome and health-related quality of life of patients after simultaneous pancreas-kidney transplantation - Scheuermann, Uwe (Health Qual Life Outcomes, 2020)
BACKGROUND: Simultaneous pancreas-kidney transplantation (SPKT) profoundly improves the health-related quality of life (HRQoL) of recipients. However, the influence of the pre-transplant dialysis modality on the success of the SPKT and post-transplant HRQoL remains unknown. METHODS: We analyzed the surgical outcome, long-term survival, as well as HRQoL of 83 SPKTs that were performed in our hospital between 2000 and 2016. Prior to transplant, 64 patients received hemodialysis (HD) and nineteen patients received peritoneal dialysis (PD). Physical and mental quality of life results from eight basic scales and the physical and mental component summaries (PCS and MCS) were measured using the Short Form 36 (SF-36) survey. RESULTS: Peri- and postoperative complications, as well as patient and graft survival were similar between the two groups. Both groups showed an improvement of HRQoL in all SF-36 domains after transplantation. Compared with patients who received HD before transplantation, PD patients showed significantly better results in four of the eight SF-36 domains: physical functioning (mean difference HD - PD: − 12.4 ± 4.9, P = < 0.01), bodily pain (− 14.2 ± 6.3, P < 0.01), general health (− 6.3 ± 2.8, P = 0.04), vitality (− 6.8 ± 2.6, P = 0.04), and PCS (− 5.2 ± 1.5, P < 0.01) after SPKT. In the overall study population, graft loss was associated with significant worsening of the HRQoL in all physical components (each P < 0.01). CONCLUSIONS: The results of this analysis show that pre-transplant dialysis modality has no influence on the outcome and survival rate after SPKT. Regarding HRQoL, patients receiving PD prior to SPKT seem to have a slight advantage compared with patients with HD before transplantation.